INDEKS KEANEKARAGAMAN JENIS SERANGGA PADA TANAMAN TEMBAKAU (Nicotiana tabaccum L.) DI KEBUN HELVETIA PT. PERKEBUNAN NUSANTARA II - Maria Magdalena Tambunan; Mena Uly Mena Uly; Hasanuddin Hasanuddin (Universitas Sumatera Utara, 2013)
Index of Insect Varieties on Tobacco Plant (Nicotiana tabaccum L.) at Kebun Helvetia, PTPNusantara II. Deli tobacco is a strategic commodity in Indonesia. Especially used to cigar wrapper(most quality) that make job vacancy and increase people prosperity. Pests and plant diseases intobacco plant was the most problem each cultivating season. By knowing insect status in tobaccoarea hoped can do preventative on next cultivating season. The objective of this research was tostudy index of insect varieties in the tobacco plant (Nicotiana tabaccum L.) at Kebun Helvetia withwas to know kind of usefull insect, useless insect, parasitoid and predator in that area. Researchconducted at Kebun Helvetia PT Nusantara II, Medan on May – June 2012, using design surveiwith take diagonally which first sample was taken in the middle of sample block. The result ofresearch showed that in Block D was consist of 15 useless insect family, 2 parasitoid family, 7predator family and 6 usefull insect family. Block E area consist of 15 useless insect family, 3parasitoid family, 8 predator family, and 8 usefull insect familiy. Shanon-Weiner (H’) highestIndex varieties value of insect highest in Block E area is 2.3486 (medium) that meaning natural andpest insect existence was balance nearly.Keywords : index of varieties, insect in tobacco, tobacco.